Status Epilepticus in Immature Rats Is Associated with Oxidative Stress and Mitochondrial Dysfunction - Folbergrová, Jaroslava; Ješina, Pavel; Kubová, Hana; Druga, Rastislav; Otáhal, Jakub (Frontiers in Cellular Neuroscience, 2016)
Epilepsy is a neurologic disorder, particularly frequent in infants and children where it can lead to serious consequences later in life. Oxidative stress and mitochondrial dysfunction are implicated in the pathogenesis of many neurological disorders including epilepsy in adults. However, their role in immature epileptic brain is unclear since there have been two contrary opinions: oxidative stress is age-dependent and does not occur in immature brain during status epilepticus and, on the other hand, evidence of oxidative stress in immature brain during a specific model of status epilepticus. To solve this dilemma, we have decided to investigate oxidative stress following status epilepticus induced in immature 12-day-old rats by three substances with a different mechanism of action, namely 4-aminopyridine, LiCl-pilocarpine or kainic acid. FluoroJade-B staining revealed mild brain damage especially in hippocampus and thalamus in each of the tested models. Decrease of glucose and glycogen with parallel rises of lactate clearly indicate high rate of glycolysis, which was apparently not sufficient in 4-AP and Li-Pilo status, as evident from the decreases of PCr levels. Hydroethidium method revealed significantly higher levels of superoxide anion (by 60 %) in the hippocampus, cerebral cortex and thalamus of immature rats during status. Status epilepticus lead to mitochondrial dysfunction with a specific pronounced decrease of complex I activity that persisted for a long period of survival. Complex II and IV activities remained in the control range. Antioxidant treatment with SOD mimetic MnTMPYP or peroxynitrite scavenger FeTPPS significantly attenuated oxidative stress and inhibition of complex I activity. These findings bring evidence that oxidative stress and mitochondrial dysfunction are age and model independent, and may thus be considered a general phenomenon. They can have a clinical relevance for a novel approach to the treatment of epilepsy, allowing to target the mechanisms which play a crucial or additive role in the pathogenesis of epilepsies in infants and children.